Clinical spectrum and management of dystonia in patients with Japanese encephalitis: A systematic review - Roshan Aryal; Suraj Shrestha; Sushan Homagain; Sunit Chhetri; Kshitiz Shrestha; Sanjeev Kharel; Ragesh Karn; Reema Rajbhandari; Bikram Prasad Gajurel; Rajeev Ojha (Brain and Behavior, 2022)
Abstract Background Japanese encephalitis (JE) is a potentially fatal viral infection with a wide range of manifestations and can also present with a variety of movement disorders (MD) including dystonia. Dystonic features in JE are uncommon. Here, we have tried to summarize the clinical features and management of dystonia among JE patients with a comprehensive literature search. Methods Various databases, including PubMed, Embase, and Google Scholar, were searched against the predefined criteria using suitable keywords combination and boolean operations. Relevant information from observational and case studies was extracted according to the author, dystonic features, radiological changes in the brain scans, treatment options, and outcome wherever provided. Result We identified 19 studies with a total of 1547 JE patients, the diagnosis of which was confirmed by IgM detection in serum and/or cerebrospinal fluid in the majority of the patients (88.62%). 234 (15.13%) of JE patients had dystonia with several types of focal dystonia being present in 131 (55.98%) either alone or in combination. Neuroimaging showed predominant involvement of thalami, basal ganglia, and brainstem. Oral medications including anticholinergics, GABA agonists, and benzodiazepines followed by botulinum toxin were the most common treatment modalities. Conclusion Dystonia can be a disabling consequence of JE, and various available medical therapies can significantly improve the quality of life. Owing to insufficient studies on the assessment of dystonia associated with JE, longitudinal studies with a larger number of patients are warranted to further clarify the clinical course, treatment, and outcome of dystonia.